Impact of aging on alanine aminotransferase levels and frailty in chronic kidney disease patients: laboratory-based cross-sectional study in Northwest Ethiopia - Melaku Mekonnen Agidew; Anemut Tilahun Mulu; Awgichew Behaile Teklemariam; Misganaw Asmamaw Mengstie; Addisu Melake; Edgeit Abebe Zewde; Zelalem Tilahun Muche; Samuel Berihun Dagnew; Nega Dagnew Baye; Bezawit Adane; Muluken Walle; Girma Derso (Frontiers in Medicine)
BackgroundChronic kidney disease (CKD) is a non-communicable progressive condition that leads to a gradual decline in kidney functions, resulting in different complications. Serum alanine aminotransferase (ALT) is an important biomarker for diagnosing liver comorbidities. However, ALT levels in CKD patients could be affected by aging. Despite this challenge, there is a scarcity of data on the effect of aging on frailty and ALT levels in CKD patients in Ethiopia. Thus, this study aimed to assess the impact of aging on serum levels of ALT, the magnitude of frailty, and the associated factors among CKD patients in different age groups.MethodsA hospital-based cross-sectional study involving 120 CKD patients was conducted in Bahir Dar, Ethiopia. Data were collected using structured questionnaire. Blood pressure, anthropometric parameters, ALT levels, and frailty were assessed according to standard procedures. Data were analyzed using SPSS version 25. Pearson’s correlation analysis, multiple linear analysis, and logistic regression analysis were performed to identify predictors of ALT levels and frailty, with a statistical significance level of p < 0.05.ResultsThe serum level of ALT was significantly lower in CKD patients aged ≥ 46 years compared to CKD patients aged 18–45 years. The magnitude of frailty in CKD patients aged 18–45 and ≥ 46 years was 8.5% (95% CI: 1.4–15.6) and 34.4% (95% CI: 22.5–46.4), respectively, and was significantly associated with ALT levels. Factors such as age category (AOR: 0.16, 95% CI: 0.04–0.60) and hypertension (HTN) (AOR: 10.16, 95% CI: 1.03–99.90) were significantly associated with frailty.ConclusionThe serum level of ALT was significantly correlated with age and frailty in CKD patients. Thus, ALT levels can be used as a biomarker for aging and frailty. The age of CKD patients and HTN were factors significantly associated with frailty.